Food and Nutrition Surveillance System (SISVAN) coverage, nutritional status of older adults and its relationship with social inequalities in Brazil, 2008-2019: an ecological time-series study - Brena Barreto Barbosa; Valéria Troncoso Baltar; Rogério Lessa Horta; Jackeline Christiane Pinto Lobato; Luiza Jane Eyre de Souza Vieira; Caroline de Oliveira Gallo; Antonio Augusto Ferreira Carioca (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to analyze the temporal trend of Food and Nutrition Surveillance System (Sistema de Vigilância Alimentar e Nutricional - SISVAN) coverage and the nutritional status of older adults, and its correlation with indicators of social inequality in Brazil between 2008-2019. Methods: this was an ecological study using records from SISVAN, related to the population aged 60 years and older; the temporal trend of coverage and the correlation between indicators of social inequality and increment rate of nutritional status were analyzed; slope index of inequality and concentration index were used to measure absolute and relative inequalities. Results: 11,587,933 records were identified; national coverage increased from 0.1% (2008) to 2.9% (2019), with a statistically significant upward trend; a moderate inverse correlation with an annual increment rate of overweight between human development index and gross domestic product per capita, was found. Conclusion: there was an increasing trend in SISVAN coverage; the increase in overweight was associated with social inequality.